Calculation of probability of winning and number of games played for various tournament formats of the world baseball classic - Hirotsu, N.; Osawa, K.; Miyaji, C. (International Journal of Computer Science in Sport, 2015)
The third World Baseball Classic (WBC) was held in March 2013. In this tournament, 16 teams play in Round 1 under a round-robin (RR) format and 8 teams which advanced to Round 2 play under a modified double-elimination (MDE) format. This 2013 WBC format is compared with the formats such as the past two WBCs held in 2006 and 2009, from the aspect of the probability of winning the tournament and the probability distribution of the number of games played by the same teams. We make the comparison by changing the relative strength of teams, and demonstrate the difference between the tournament formats.